What are the requirements for developing a successful national registry of auditory implants? A qualitative study. Issue 9 (12th September 2018) - Mandavia, Rishi; Knight, Alec; Carter, Alexander W; Toal, Connor; Mossialos, Elias; Littlejohns, Peter; Schilder, Anne GM
Abstract : Objectives: Hearing loss is an area of unmet need, and industry is targeting this field with a growing range of surgically implanted hearing devices. Currently, there is no comprehensive UK registry capturing data on these devices; in its absence, it is difficult to monitor clinical and cost-effectiveness and develop national policy. Recognising that developing such a registry faces considerable challenges, it is important to gather opinions from stakeholders and patients. This paper builds on our systematic review on surgical registry development and aims to identify the specific requirements for developing a successful national registry of auditory implants. Design: Qualitative study. Participants: Data were collected in two ways: (1) semistructured interviews with UK professional stakeholders; and (2) focus groups with patients with hearing loss. The interview and focus group schedules were informed by our systematic review on registry development. Data were analysed using directed content analysis. Judges mapped the themes obtained against a conceptual framework developed from our systematic review on registry development. The conceptual framework consisted of five categories for successful registry development: (1) planning, (2) registry governance, (3) registry dataset, (4) anticipating challenges, (5) implementing solutions. Results: Twenty-seven themes emerged from 40 semistructured interviews with professional stakeholders and 18 themes emerged from three patient focus groups. The most important factor for registry success was high rates of data completion. Benefits of developing a successful registry of auditory implants include: strengthening the evidence base and regulation of auditory implants, driving quality and safety improvements, increased transparency, facilitating patient decision-making and informing policy and guidelines development. Conclusions: This study identifies the requirements for developing a successful national registry of auditory implants, benefiting from the involvement of numerous professional stakeholder groups and patients with hearing loss. Our approach may be used internationally to inform successful registry development.